1962
DOI: 10.1063/1.1732338
|View full text |Cite
|
Sign up to set email alerts
|

Shock-Tube Study of the Kinetics of Nitric Oxide at High Temperatures

Abstract: A shock-tube program was carried out in which the NO concentration was followed as a function of time behind the shock front by absorption of 1270 A radiation, where ground vibrational state O2 and N2 are essentially transparent. The absorption coefficients of the species NO, O2, and N2 as functions of the respective vibrational temperatures were determined by measuring the absorption by the shock-heated gas at a point in the time history corresponding to complete vibrational relaxation but before the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…The subsequent measurements of Thielen and Roth (1984) are quite close to the earlier work of Wray and Teare (1962) (Figure 2.2). While the higher values of Koshi et ai.…”
Section: 6supporting
confidence: 86%
“…The subsequent measurements of Thielen and Roth (1984) are quite close to the earlier work of Wray and Teare (1962) (Figure 2.2). While the higher values of Koshi et ai.…”
Section: 6supporting
confidence: 86%
“…The only two reported rates for k.; are based mainly on the results on either reaction (I) or (2). Wray and Teare (1962) calculated k_ l from the Downloaded by ["Queen's University Libraries, Kingston"] at 22:12 03 February 2015 equilibrium constant and the k 1 reported by Freedman and Daiber (1961); they found that this rate gave an adequate fit of their data (NO/AI' and air/AI' mixtures). Camac and Feinberg (1967), on the other hand, from their studies on shock heated air in which an induction period was observed before the NO increase and on pure NO decomposition deduced that k_ 1 should be at least 10 times lower than the value proposed by Wray and Teare (1962).…”
Section: Discussionmentioning
confidence: 99%
“…The list is not exhaustive but contains most of those reported in studies on NO decomposition and formation. Baulch et al (1970) and Lipkea et al (1973) Kistiakowsky et al (1969) Fishburne and Edse (1966 Wray and Teare (1962) Wray and Teare (1962) Wray and Teare (1962) Watt and Myerson (1969) Wray and Teare (1962) In the absence of actual experimental results, the rate constant chosen is generally the most recently reported for conditions as close as possible to those in the simulation. This criterion was used in assigning the rate reported by Wagner et al (1966) for reaction (4) since it has been confirmed in the recent shock tube study of N.O decomposition (Ne diluent) by Kistiakowsky et al (1969).…”
Section: No Decomposition Simulationmentioning
confidence: 99%
“…However, the emphasis of the paper is mostly on the implementation of an advanced model for reaction ͑1͒ in a computational fluid dynamics ͑CFD͒ code. The first Zeldovich reaction ͓reaction ͑1͔͒, although much studied experimentally [6][7][8][9][10][11] in the combustion temperature range ͑TϽ5000 K͒, has not been investigated at higher temperatures and under nonequilibrium conditions. Recently, an extensive quasiclassical trajectory ͑QCT͒ study of this reaction was completed by the authors, 12-14 based on accurate ab initio potential energy surfaces.…”
Section: Introductionmentioning
confidence: 99%